(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Enteric fever caused by Salmonella species is a systemic febrile illness that can be fatal since its characterization in 1880. Enteric fever may remain asymptomatic carrier and sometimes fatal that it can be difficult to diagnose based on symptoms alone because they are similar to those of other febrile disorders. In developing countries, enteric fever is common global health problem due to poor standard of personal hygiene, contaminated food, inadequate safe water and sanitation. Methods: This is a cross-sectional study that was conducted in the Microbiology Department of Rajshahi Medical College Hospital for one year from January 2021 to December 2021 to identify Salmonella species by Automated Blood Culture (Fastidious Antibiotic Neutralization method) followed by subculture in MacConkey’s agar, Xylose lysine deoxycholate agar, and Salmonella Shigella agar media in suspected enteric fever cases. This study included suspected cases of enteric fever as determined by the physician who fulfilled the inclusion and exclusion criteria. Results: Among 127 suspected cases of enteric fever 64(50.39%) culture positive bacteria isolated by automated blood culture (FAN) method and out of that Salmonella species 38 (59.37%) and others bacteria 26(40.63%) following subculture in MacConkey’s agar, Xylose lysine deoxycholate agar and Salmonella Shigella agar media. Regarding gender, the majorities (61.4%) of culture-positive patients were male, and the majority (65.35%) came from rural areas. Conclusion: Especially for patients who have received antibiotics, we propose that the automated blood culture approach followed by subculture could be employed as a novel diagnostic method for typhoid fever. TAJ 2023; 36: No-2: 71-76